2017
DOI: 10.17116/terarkh2017898113-119
|View full text |Cite
|
Sign up to set email alerts
|

Kagocel in the therapy of influenza and acute respiratory viral infections: Data analysis and systematization from the results of preclinical and clinical trials

Abstract: The article provides the summarized data of clinical trials evaluating the efficacy and safety of kagocel used to prevent and treat influenza and acute respiratory viral infections of different etiologies. The results of numerous preclinical and clinical trials suggest that the kagocel substance is highly safe and that it is appropriate to use the drug for the treatment and prevention of influenza and acute respiratory viral infections of another etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…This method ensures reliable detection of free gossypol impurity with high accuracy and precision at minimum amounts starting from 1.56•10-5 mg/mL. The specified method sensitivity is in line with the international publications on HPLC assay of gossypol (11,23). It should be mentioned that the method validation demonstrated that whole gossypol amount added to the substance from outside is reliably and accurately identified in this complex evidencing lack of nonspecific sorption of its free molecules on polymeric matrix.…”
Section: Manufacturing Quality Controlsupporting
confidence: 62%
See 2 more Smart Citations
“…This method ensures reliable detection of free gossypol impurity with high accuracy and precision at minimum amounts starting from 1.56•10-5 mg/mL. The specified method sensitivity is in line with the international publications on HPLC assay of gossypol (11,23). It should be mentioned that the method validation demonstrated that whole gossypol amount added to the substance from outside is reliably and accurately identified in this complex evidencing lack of nonspecific sorption of its free molecules on polymeric matrix.…”
Section: Manufacturing Quality Controlsupporting
confidence: 62%
“…Acute toxicity study allows to determine tolerable, toxic and lethal doses of test product administered inragastrically, establish the causes of animal mortality during 14-day follow-up period, investigate its effect on general condition and a number of functional and morphological parameters. It should be noted that intoxication signs in acute toxicity study of free gossypol has been investigated thoroughly including respiratory distress, body weight changes, anorexia, weakness, apathy, signs of cardiac failure and death several days later (11). At that, the data from acute toxicity study of Kagocel revealed no animal mortality and no signs of acute intoxication were detected either.…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory tract infections may be caused by bacteria, viruses and parasites (4)(5)(6), although viruses are thought to be responsible for the majority (approximately 20-60%) of these infections (7)(8)(9). Viral agents that are mostly involved include the respiratory syncytial virus (RSV), influenza A/B, rhinovirus, adenovirus, Eppstein-Barr virus (EBV) and cytomegalovirus (CMV), while the most common atypical agents are Streptococcus pneumoniae, Haemophilus influenzae, Mycoplasma pneumoniae (M pneumoniae), Chlamydophila pneumoniae (C pneumoniae), and Legionella pneumophila (10)(11)(12)(13). Also, several Herpes viruses such as Herpes simplex virus 1 (HSV1), Herpes simplex virus 2 (HSV2) and Human Herpesvirus 6 (HHV6) have been reported to be potentially associated with acute RTIs (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Карбоксиметилцеллюлоза снижает токсичность госсипола и обеспечивает мембранный контакт препарата с клеточной поверхностью. В клинических исследованиях была подтверждена безопасность препарата Кагоцел ® ; в настоящее время он широко применяется в России для профилактики и лечения респираторных вирусных инфекций и герпеса [4,5].…”
unclassified